Ireland : Request for an Extended Arrangement-Staff Report; Staff Supplement; Staff Statement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The economic and financial pressures facing Ireland are intense. The banking sector is at the fulcrum of Ireland's problems. The program, therefore, aims to restore the banking system. It will address structural problems and restore confidence. A leaner and more robust banking sector is the major objective. The program provides support in the transition through additional capital to banks. The credibility of the banking system will be bolstered by stringent stress and diagnostic tests. The substantial risks to the program will need to be actively managed.